1992
DOI: 10.1182/blood.v80.6.1521.1521
|View full text |Cite
|
Sign up to set email alerts
|

Unusual diffuse liver fibrosis accompanying transient myeloproliferative disorder in Down's syndrome: a report of four autopsy cases and proposal of a hypothesis

Abstract: Transient myeloproliferative disorder (TMD), an acute leukemia-like disorder in neonates with Down's syndrome, is characterized by spontaneous regression of abnormal blast growth. Because proliferating blasts frequently express phenotypes of megakaryocytic lineage and, as a result, this disorder resembles acute megakaryoblastic leukemia (AMKL), it would be of interest to determine whether myelofibrosis, a common complication of AMKL, is also present in TMD. Pathologic observations of four autopsy cases of TMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 1 publication
5
53
1
3
Order By: Relevance
“…Down syndrome with TMD is sometimes associated with liver fibrosis, which usually takes a lethal course (2)(3)(4).…”
Section: Resultsmentioning
confidence: 99%
“…Down syndrome with TMD is sometimes associated with liver fibrosis, which usually takes a lethal course (2)(3)(4).…”
Section: Resultsmentioning
confidence: 99%
“…It may be the cause of stillbirth in DS. In one series of eight patients with the complication, two were long-term survivors (Miyauchi et al, 1992). Infants may die of fulminant liver failure while the TMD is regressing.…”
Section: Transient Myeloproliferative Disordermentioning
confidence: 99%
“…Extensive myelofibrosis and generalized visceral fibrosis are occasionally present (Becroft & Zwi, 1990;Zipursky et al, 1992). Miyauchi et al (1992) offered an interesting theory: the signs and symptoms of hepatic fibrosis may dominate TMD because the leukaemic blasts arise from fetal hepatic blood-forming cells. Normally, the transition from hepatic to medullary myelopoiesis accompanies the regression of TMD.…”
Section: Transient Myeloproliferative Disordermentioning
confidence: 99%
“…Massive hepatomegaly (beyond the umbilicus) was almost completely confined to the high-risk group. Miyauchi et al (1992) reported a series of 8 cases of TL-DS, of whom 6 died due to hepatic disease. In those who died, mean conjugated bilirubin at presentation was 84 lmol/l (42-122), progressing to a mean of 319 lmol/l (158-400) at the time of death.…”
Section: Indications For Treatment Of Tl-dsmentioning
confidence: 99%